Food security within covid-19 period - Siew, Phui Qi (2025)
Food Security is important to both health and economy. Since the number of people who face food security is showing an upward trend, food security has become a global concern. The Covid-19 pandemic exacerbated global food security by increasing the unemployment rate, disruption in food supply chains, and rise in food prices. As a result, this study aims to examine the relationship between unemployment rate, supply chain disruptions, rising food prices, and food security in countries with moderate Global Food Security Index (GFSI) scores ranging from 50% to 79.9% from 2018 to 2022. Food security is the dependent variable, unemployment rate, supply chain disruptions, and rising food prices are the independent variables, while GDP per capita and population growth rate serves as the control variables. This study employed quantitative research and panel data methodology. All the data are collected from official sources such as the EIU, World Bank, Federal Reserve Bank of New York, IMF, and OECD. The results of this study indicate that the rising food prices and GDP per capita has a significant and positive relationship with food security. However, the unemployment rate, supply chain disruptions, and population growth rate do not have a significant relationship with food security, which means that these variables do not affect the food security of the observed countries during the pandemic. The findings can provide guidance to the governments worldwide to improve food security in their countries.